Isolation, kinetics, and performance of a novel phenol degrading strain - Zhang, Wen (Array, 2020)
Efficient phenol-degrading bacteria is still the key to the biological treatment of phenol-containing wastewater. In this research, a novel phenol-degrading strain N8 was isolated. According to the 16S rDNA identification, it was concluded that the N8 strain was Bacillus sp. IARI-J-20. The wastewater treatment experiments showed that the phenol degrading rate of N8 reached 92.8 % at 24 h with the inoculation amount of 15 %, temperature of 30 °C, pH of 7.2, yeast extract addition of 0.08 %, and initial phenol concentration of 225 mg L–1. Haldane’s model was fit for the growth kinetics of the phenol-degrading strain N8 over a wide range of initial phenol concentrations (50–1200 mg L–1), with kinetic values μmax = 0.33 h−1, Ks = 79.16 mg L–1, and Ki = 122 mg L–1. The yield coefficient reached maximal value when the phenol concentration was 400 mg L–1. When the initial phenol concentration was more than 400 mg L–1, the inhibition effect of phenol became predominant.